Reviving the true meanings & applications of Islam, Iman & Ihsan: contextualising & relevantising al-din in the contemporary world - Muhammad Uthman El-Muhammady, Asma; Hassan, Nur Jannah; Maromar, Fahed (2018)
This paper attempts to revive the observation of the true meanings and applications of Islām, Īmān and Iḥsān as an integrated system of life, consisting of the internal and the external constituents of the Dīn al-Islām. The whole aspect of the Dīn lies in these three interconnected fundamental concepts making it applicable and suitable at all times and in all places. Beginning with a brief prologue to each term, the paper then discusses aspects of the Dīn and of life – from the very basis of relationships between a human being and his person, his families, his society in all its levels (ḥabl min al-nās) and his immediate and extended environments [ḥabl min al-kawn], to his vertical connection with his Creator (ḥabl min Allāh) and his destiny in the next world – all lie within these three fundamental elements of the religion. Islām, while binding humankind directly to his Creator through his daily and regular acts of obedience, it instructs him on how to deal with his very self as well as with the rest of humanity, and how he is connected to the world, its animate and inanimate inhabitants, and to the rest of the Cosmos, both physical and unseen--the last point brings to Īmān. Humankind is the khalīfah (vicegerent) of God whose office of duty is this world. He is an active agent of the Divine Will in the physical world. Iḥsān is a system that governs human decisions and actions at all levels, making him fit in the face of the ever-changing and fluctuating world, thus making him resilient. It consolidates him in his service as God’s instrument on earth. This total package of Islam, if it is entirely understood and applied in life, places humanity firmly on the straight path as he treads along his Divinely ordained vocation as khalīfah of God on earth.